Peer interaction and its influence on the adoption of green products: A study based on demographic characteristics of respondents in Punjab - Dr.RajeevPrasher, (The journal of contemporary issues in business and government, 2021)
Ecological consciousness is increasing in society with every passing day. The factors that influence purchase behavior of green products need deeper understanding. The reason is that the underlying dynamics behind people’s buying behavior for green products is not easy difficult comprehend. This study attempts to investigate the impact of peer interaction on the green perceived value and the influence of ecological consciousness on green buying behavior amongst people of diverse demographic characteristics. The primary data has been collected from respondents using structured questionnaire from the students of universities and schools and teachers and other employees of varied socioeconomic characteristics. Statistical tools such as t-test, ANOVA and Post Hoc test for multiple- comparisons are employed for analysis. The present study finds that peer interaction has greater influenceon the younger generation towards purchase of green products. The study also investigates green buying behavior stimulated by ecological consciousness among persons of varied demographic characteristics.